Personal protective equipment for use in a filovirus disease outbreak : rapid advice guideline - Den Boon, Saskia (World Health Organization, 2016)
This document provides a summary of recommendations for personal protective equipment to be used by health workers providing clinical care for patients with filovirus infection (Ebola and Marburg).
Keywords: Health Workforce; zdravotničtí pracovníci; Marburgvirus; Protective Devices; Filoviridae Infections; virus Ebola; přenos infekce z pacienta na zdravotnického pracovníka; Infectious Disease Transmission, Patient-to-Professional; Ebolavirus; infekční lékařství; infekce viry z čeledi Filoviridae; bezpečnostní opatření; pracovní lékařství; Security Measures; virus Marburg; ochranné prostředky